Interest limitation rules and business cycles: Empirical evidence - Olli Ropponen (The Research Institute of the Finnish Economy (ETLA), 2021)
This paper studies the performance of interest limita- tion rules during business cycles. It employs register data on Finnish affiliates of multinational enterprises (MNEs) to study both thin-capitalization rules (TCRs) and earnings-stripping rules (ESRs). Both types of rules are found to become tighter in economic downturns: TCRs due to higher debt-to-equity ratios and ESRs due to lower company profits. Among equally tight interest limitation rules, TCRs are found to provide less variation and less pro-cyclical outcomes by increasing the compa- ny tax burden less than ESRs in an economic downturn. While ESRs increase the tax burden of Finnish compa- nies by 17.5%-19.3% following the 2008 global financial crisis, for TCRs the increase is less than 10%. Among the ESRs, we find that an EBIT rule induces tighter tax treat- ment in economic downturns than an EBITDA rule. How- ever, the differences between ESRs remain very small.
Keywords: H25; H26; F44; 330; Business cycles; Corporate income taxation; Anti-tax avoidance rules; Thin-Capitalization Rules (TCRs); Earnings Stripping Rules (ESRs)